The Devil’s in the Details—or Is He?: the Ethics and Politics of Terrorism Data - Allison, Benjamin V. (Perspectives on terrorism, 2021)
In the United States, domestic political violence has become a focal point of discourse among scholars, policy makers, journalists, politicians, and the public. This is largely due not only to the recent increase in domestic terrorist plots and attacks by ideological extremists, but also to the recent civil unrest surrounding the COVID-19 lockdowns, Black Lives Matter protests, and the 2020 presidential election. As think tanks like New America and the Center for Strategic and International Studies have compiled data and produced reports to inform this discourse, they have made some serious missteps in their coding of data. Between omitting conflict events and miscoding the ideology of perpetrators in such a way as to obscure the violence of left-wing, Black separatist/nationalist/supremacist, and anti-White extremists, they unintentionally give the impression of political bias in their coding, thereby undermining their credibility in the eyes of a public that is increasingly skeptical of experts. This article identifies some of these data problems and discusses their implications.